2018
DOI: 10.1002/bip.23119
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic polymers as substrates for a DNA‐sliding clamp protein

Abstract: The clamp protein (gp45) of the DNA polymerase III of the bacteriophage T4 is known to bind to DNA and stay attached to it in order to facilitate the process of DNA copying by the polymerase. As part of a project aimed at developing new biomimetic data‐encoding systems we have investigated the binding of gp45 to synthetic polymers, that is, rigid, helical polyisocyanopeptides. Molecular modelling studies suggest that the clamp protein may interact with the latter polymers. Experiments aimed at verifying these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Loading studies with the clamp‐loader protein complex gp44/gp62 showed that clamp gp45 did not load onto polyethyleneimine, but could load onto PIAA and PIAAA. The latter polymer proved to be the best substrate, outperforming even blunt DNA, which is the best natural analog [18b] . Experiments in which a gp45 clamp modified with catalytic functions processively modifies a PIAAA polymer have not been reported so far.…”
Section: Synthetic Processive Catalystsmentioning
confidence: 99%
“…Loading studies with the clamp‐loader protein complex gp44/gp62 showed that clamp gp45 did not load onto polyethyleneimine, but could load onto PIAA and PIAAA. The latter polymer proved to be the best substrate, outperforming even blunt DNA, which is the best natural analog [18b] . Experiments in which a gp45 clamp modified with catalytic functions processively modifies a PIAAA polymer have not been reported so far.…”
Section: Synthetic Processive Catalystsmentioning
confidence: 99%